2019
DOI: 10.1039/c9ra04843j
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA ZFAS1 enhances adriamycin resistance in pediatric acute myeloid leukemia through the miR-195/Myb axis

Abstract: Long noncoding RNA ZFAS1 silencing alleviated ADR resistance of AML cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In pediatric acute myeloid leukemia (AML), ZFAS1 elevates resistance to Adriamycin (ADR) as a frequent chemotherapeutic. According to studies, ADR promotes ZFAS1 in pediatric AML, and knockdown of ZFAS1 or Myb diminishes ADR resistance in vitro [ 72 ]. ZFAS1 directly interacts with miR-195, which regulates Myb to increase ADR resistance in pediatric AML [ 73 ].…”
Section: The Role Of Zfas1 In Chemoresistancementioning
confidence: 99%
See 1 more Smart Citation
“…In pediatric acute myeloid leukemia (AML), ZFAS1 elevates resistance to Adriamycin (ADR) as a frequent chemotherapeutic. According to studies, ADR promotes ZFAS1 in pediatric AML, and knockdown of ZFAS1 or Myb diminishes ADR resistance in vitro [ 72 ]. ZFAS1 directly interacts with miR-195, which regulates Myb to increase ADR resistance in pediatric AML [ 73 ].…”
Section: The Role Of Zfas1 In Chemoresistancementioning
confidence: 99%
“…ZFAS1 directly interacts with miR-195, which regulates Myb to increase ADR resistance in pediatric AML [ 73 ]. Therefore, ZFAS1 may be a diagnostic or therapeutic marker for ADR resistance in pediatric AML [ 72 ].…”
Section: The Role Of Zfas1 In Chemoresistancementioning
confidence: 99%
“…The p15 INK4B /p16 INK4A repressor ANRIL was recently suggested to contribute to leukaemia progression by increasing glucose metabolism (Sun et al , ). Additionally, zinc finger antisense 1 ( ZFAS1 ) was shown to mediate doxorubicin resistance in paediatric AML via inhibition of miR‐195 and subsequent upregulation of MYB (Li & Wang, ). Low expression and promoter hypermethylation of MEG3 is associated with poor prognosis in AML, and it was recently shown that mutations in TET2 or WT1 substantially reduce MEG3 levels (Lyu et al , ).…”
Section: Epigenetic Dysregulation In Paediatric Amlmentioning
confidence: 99%
“…Dysregulation of lncRNAs (such as lncRNA CRNDE, KCNQ1OT1, and ZFAS1) is implicated in chemoresistance in AML [10][11][12][13]. Long intergenic non coding RNAs (lincRNAs), a type of lncRNA, are emerging as key regulators in cancer development.…”
Section: Introductionmentioning
confidence: 99%